Economic Feasibility Study on PV/Wind Hybrid Microgrids for Indonesia Remote Island Application - Syafii Syafii (UIKTEN, 2021)
This paper presents the economic feasibility of hybrid microgrid power system for three remote islands of Sumatra, Indonesia. The microgrid system simulated and analysed using Homer Pro software. Optimization results showed that the combination of photovoltaic (PV), diesel generation (G) and batteries (Batt) for microgrid power system in Mandeh and Lagundri Island area were the most economical configuration. Meanwhile, for Mentawai area, the combination of PV, Wind Turbine (WT), G, Batt was the most optimal since it has higher wind speed then the other two areas. The Mandeh area has the highest solar radiation compared to the other two areas, resulting in the lowest CoE of $0.096/kWh as well as the lowest investment and operational costs. For the fixed PV 100 kW scenario, the optimal configuration is obtained with 86 kW supplied by WT for the Lagundri location, and 67 kW supplied by WT for the Mentawai area, while the WT installation area is not recommended for Mandeh location. The power management analysis showed that the average and patterns of weather parameters including solar radiation and wind speed effect both PV and Wind electrical power production.